2020
DOI: 10.1186/s12859-020-3480-3
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical discovery of large-scale and focal copy number alterations in low-coverage cancer genomes

Abstract: Background: Detection of DNA copy number alterations (CNAs) is critical to understand genetic diversity, genome evolution and pathological conditions such as cancer. Cancer genomes are plagued with widespread multi-level structural aberrations of chromosomes that pose challenges to discover CNAs of different length scales, and distinct biological origins and functions. Although several computational tools are available to identify CNAs using read depth (RD) signal, they fail to distinguish between large-scale … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…The CNV caller module identifies CNVs in cancer cell lines using the RD signal computed by the RD calculator module. It incorporates the multimodal RD signal modeling approach of CNAtra [ 23 ] to hierarchically identify large-scale and focal CN-altered segments. These CN events are integrated to generate the CNV track that is used as an explicit bias source for correcting chromatin interaction matrix.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The CNV caller module identifies CNVs in cancer cell lines using the RD signal computed by the RD calculator module. It incorporates the multimodal RD signal modeling approach of CNAtra [ 23 ] to hierarchically identify large-scale and focal CN-altered segments. These CN events are integrated to generate the CNV track that is used as an explicit bias source for correcting chromatin interaction matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Overall results showed that midpoint and exact-cut approaches failed to capture RD signal amplitude change in many cases. Considering the CNVs identified by CNAtra [ 23 ] (ref) using WGS datasets of MCF7 and LNCaP as ground truth, HiCNAtra’s CNV caller outputs using midpoint and exact-cut approaches resulted in several false negatives. For example, in the MCF7 chr 1 (80–100 Mb) region, HiCNAtra’s CNV caller output using the entire-fragment counting method revealed high concordance with the CNAtra’s WGS-derived CNV output of the same cell line.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations